2016
DOI: 10.3221/igf-esis.38.41
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour and durability of high volume fly ash cementitious composites

Abstract: The purpose of this research is to separate different morphological particles of ASTM class F fly ash, and study their effect on mechanical behaviour and durability of high volume cementitious mixtures. In this research wet separation of raw fly ash is carried out, which resulted in three layers of different morphological particles. The first layer of particles float, comprise of about 1-5% of fly ash, is identified as cenospheres or hollow spheres. The second layer of particles is measured to be 55-60% of raw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In raw fly ash FE-SEM image of Fig. 3 (a), it is observed that raw fly ash consists of several type of particles including glassy hollow spherical, solid spherical, porous spherical, porous slaggy, compact slaggy particles, and some brighter particles as observed by the authors in [21]. However, in Fig.…”
Section: Morphological Properties Of Separated and Milled Fly Ash Parmentioning
confidence: 73%
See 4 more Smart Citations
“…In raw fly ash FE-SEM image of Fig. 3 (a), it is observed that raw fly ash consists of several type of particles including glassy hollow spherical, solid spherical, porous spherical, porous slaggy, compact slaggy particles, and some brighter particles as observed by the authors in [21]. However, in Fig.…”
Section: Morphological Properties Of Separated and Milled Fly Ash Parmentioning
confidence: 73%
“…Wet separation of ASTM Class F brown coal raw fly ash from Počerady power plant of Czech Republic was carried out as explained in [21] and [28] by the authors as shown in Fig. 1 (a) and (b).…”
Section: Materials and Methods 21 Wet Separation And High Speed Millingmentioning
confidence: 99%
See 3 more Smart Citations